Sistem Pakar Diagnosa Penyakit Pada Kucing Menggunakan Metode Forward Chaining Berbasis Android - Rahadian Aditya Prayuda; Diah Arifah Prastiningtyas; Arif Tirtana (J-INTECH ( Journal of Information and Technology), 2021)
Zoonoses are diseases or infections suffered by animals and are naturally transmitted between vertebrates and humans. The development of zoonoses in recent years is a sign of the increasing threat of deadly diseases to humans transmitted by animals. To date, there are no less than 300 animal diseases that can infect humans. The population of domesticated cats in Indonesia is around 15 million and is in the second place with a 66% increase in the world's population [1]. However, this is not matched by the knowledge of the keepers and the availability of sufficient veterinarians. The purpose of this research is to help pet owners, especially cats, to be able to know in advance about the diseases that may attack their cats through the symptoms that arise. In its development, this system obtains data from a veterinarian expert in Malang City where there are 16 diseases that can be diagnosed by the system with 61 symptoms. The development of this system starts from literature study, data collection, data analysis, system design, to system implementation process and validity testing. From the series of studies above, the system's accuracy rate reaches 90%, which means that the system can diagnose cat disease based on symptoms properly and in accordance with the research objectives.